Ultrasound Promoted Synthesis of 3-Carboxycoumarins in Aqueous Media - Jian-Long Du; Li-Jun Li; Da-Hai Zhang (E-Journal of Chemistry)
An efficient and green procedure has been developed for synthesis of 3-carboxycoumarins, the reaction can be carried out in water under ultrasound irradiation, avoiding addition of catalyst